2020
DOI: 10.1177/2158244020947441
|View full text |Cite
|
Sign up to set email alerts
|

Intervening in Indigenous Gambling: A Systematic Review of the Literature

Abstract: Internationally, Indigenous people have higher rates of problem gambling than other population groups, yet the uptake of gambling help services is thought to be low. This may be due to the lack of culturally appropriate services and staff. This study aimed to systematically search and review the literature relating to interventions designed for Indigenous populations that seek to prevent or address gambling harm, to support the design of new programs. Peer-reviewed articles and gray literature that described p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…According to the inclusion criteria previously described, this systematic review found only eight published papers that describe and assess an intervention on RPs. Despite this low result, this is not the first time a systematic review found a huge lack of research on a given topic (e.g., Dehghanniri & Borrion, 2021;Johnson et al, 2019;Maniglio, 2008;Whiteside et al, 2020). This expressive small number of articles supports the assumption that inmates awaiting trial are usually disregarded from the efforts to treat mental and emotional health disorders and adaptation problems within prisons (Duthé et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…According to the inclusion criteria previously described, this systematic review found only eight published papers that describe and assess an intervention on RPs. Despite this low result, this is not the first time a systematic review found a huge lack of research on a given topic (e.g., Dehghanniri & Borrion, 2021;Johnson et al, 2019;Maniglio, 2008;Whiteside et al, 2020). This expressive small number of articles supports the assumption that inmates awaiting trial are usually disregarded from the efforts to treat mental and emotional health disorders and adaptation problems within prisons (Duthé et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…Two articles referred to harm reduction programs specific to Indigenous peoples [ 82 , 83 ]. Whiteside et al, (2020) conducted a systematic review of interventions in Indigenous gambling identifying four articles, only one of which provided (indeterminant) outcomes data.…”
Section: Q2 What Evidence Is There Of Impact Of Gambling-related Harm...mentioning
confidence: 99%